“We Started Over Again, We Were Young”: Postwar Social Worlds of Child Holocaust Survivors in Montreal - Sheftel, Anna; Zembrzycki, Stacey (Urban History Review / Revue d'histoire urbaine, 2010)
Thousands of child Holocaust survivors arrived in Montreal, Quebec, between 1947 and 1952, looking to remake their lives, rebuild their families, and recreate their communities. Integration was not seamless. As survivors struggled to carve spaces for themselves within the established Canadian Jewish community, their difficult wartime stories were neither easily received nor understood. When remembering this period, survivors tend to speak about employment, education, dating, integration into both the pre-war Jewish community and the larger society, and, perhaps most importantly, the creation of their own social worlds within existing and new frameworks. Forged in a transitional and tumultuous period in Quebec’s history, these social worlds, as this article demonstrates, are an important example of survivor agency.Although survivors recall the ways in which Canadian Jews helped them adjust to their new setting, by organizing a number of programs and clubs within various spaces—Jeanne Mance House, the Young Men’s and Young Women’s Hebrew Association, and the Jewish Public Library—they also speak about how they forged their own paths upon arriving in this postwar city. For instance, survivors created the New World Club, an informal and grassroots social organization where they could prioritize their own needs and begin to be understood as people, and not just survivors. Establishing the interconnections between these formal and informal social worlds, and specifically, how survivors navigated them, is central to understanding the process through which they were able to move beyond their traumatic pasts and start over. Nightmares and parties are parts of the same story, and here the focus is on the memories of young survivors who prioritized their social worlds.Anna Sheftel and Stacey Zembrzycki have created a short movie about child Holocaust survivors’ postwar social worlds, using clips from the life story interviews that they conducted with them as part of the Montreal Life Stories project. To view this movie, go to: http://citizenshift.org/we-started-over-again-we-were-young.